Role of tumour-associated macrophages in oral squamous cells carcinoma progression: an update on current knowledge - Maria Noel Marzano Rodrigues Petruzzi; Karen Cherubini; Fernanda Gonçalves Salum; Maria Antonia Zancanaro de Figueiredo (BMC, 2017)
Abstract Background Oral squamous cell carcinoma (OSCC) accounts over 90% of malignant neoplasms of the oral cavity. This pathological entity is associated to a high mortality rate that has remained unchanged over the past decades. Tumour-associated macrophages (TAMs) are believed to have potential involvement in OSCC progression. However, the molecular networks involved in communication between stroma and cancer cells have not yet been fully elucidated. Main body The role of M2 polarized cells in oral carcinogenesis is supported by a correlation between TAMs accumulation into OSCC stroma and poor clinical outcome. Signalling pathways such as the NF-κB and cytokines released in the tumour microenvironment promote a bidirectional cross-talk between M2 and OSCC cells. These interactions consequently result in an increased proliferation of malignant cells and enhances aggressiveness, thus reducing patients' survival time. Conclusions Here, we present a comprehensive review of the role of interleukin (IL)-1, IL-4, IL-6, IL-8, IL-10 and the receptor tyrosine kinase Axl in macrophage polarization to an M2 phenotype and OSCC progression. Understanding the molecular basis of oral carcinogenesis and metastatic spread of OSCC would promote the development of targeted treatment contributing to a more favourable prognosis.